ISOLATION AND MOLECULAR IDENTIFICATION OF INDIGENOUS BACTERIOCIN-PRODUCING WEISSELLA CIBARIA - Wayah, Samson Baranzan; Abubakar, Shehu; Saleh, Jamila; Alvan, Amos; Yado, Simnom (FUDMA JOURNAL OF SCIENCES, 2024)
Globally, over 6.22 million deaths are associated with antibiotic resistance. Bacteriocins, a set of antimicrobial peptides synthesized on the ribosomes, are widely viewed as a potential answer to this issue. This is due to their pore-forming ability and antimicrobial activity against antibiotic-resistant pathogens. The aim of this study is to isolate bacteriocin-producing Weissella cibaria and evaluate its antimicrobial activity against Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Salmonella typhi, Proteus mirabilis, Streptococcus sp., Candida sp. and Rhizopus stolonifer. Weissella cibaria man1 was isolated by inoculating deMan Rogosa Sharpe (MRS) broth with small pieces of ripe Mangifera indica (mango), 24-hour incubation at 370C, 10-fold serial dilution and plating on MRS agar. Molecular identification was achieved by DNA extraction, amplification of the 16S rRNA gene through polymerase chain reaction (PCR), agarose gel electrophoresis, gene sequencing, and BLASTN homology searches in the National Center for Biotechnology Information (NCBI). Antimicrobial activity of the bacteriocin was determined by agar well diffusion assay. Mangifera indica (mango) was found to harbor bacteriocin-producing Weissella cibaria man1. The bacteriocin (weissellicin man1) exhibited a broad spectrum of antimicrobial activity. Weissellicin man1 suppressed the growth of several target pathogens (Pseudomonas aeruginosa, Klebsiella pneumoniae, Salmonella typhi, Proteus mirabilis, Candida sp. and Rhizopus stolonifer) but had no inhibitory action against Escherichia coli, Streptococcus sp., Staphylococcus aureus. In conclusion, weissellicin man1 from Weissella cibaria man1 has a broad-spectrum of antimicrobial action. These findings will facilitate further evaluation of the antimicrobial potency of  weissellicin man1.